P76 Is a normal CT thorax sufficient to exclude thoracic malignancy in patients referred to fast-track clinic with haemoptysis? – Data from eight years of referrals to a large NHS teaching hospital. (12th November 2019) - Quinn, JA; Chia, WL; Raju, RS; Callister, MEJ; Kennedy, MPT
Abstract : Introduction and objectives: Unexplained haemoptysis is a red-flag symptom prompting CT imaging to exclude lung cancer. Patients with normal scans often undergo bronchoscopy despite evidence suggesting the yield is minimal. 1 We sought to determine if a normal CT thorax was sufficient to exclude a diagnosis of thoracic malignancy. Methods: We retrospectively analysed patients referred to our fast-track service between 2008–2016 and identified 834 patients presenting with haemoptysis, including 370 from a previous dataset. 2 We collected data on demographics, smoking history, upper airway symptoms, haemoptysis and reviewed radiology and bronchoscopy reports, where performed. All patients were followed-up for at least two years. We determined whether patients were diagnosed with lung cancer at time of referral or during follow-up (after 1 year). Results: Patients were grouped according to CT and bronchoscopy results. CT results were categorised as normal, benign findings, probable cancer or not performed. In 403 patients with a normal CT thorax, 46 underwent bronchoscopy. One patient, with symptoms that warranted a fast-track ENT referral, was found to have a pharyngeal cancer. No other patients were diagnosed with lung cancer within one year; 4 patients were diagnosed with lung cancer at later dates (intervals of 636–1379 days from initial CT). In 304 patients with a benign CT, 69 underwent bronchoscopy. One patient with a CT reported as having an endobronchial abnormality, likely secretions, was found to have cancer. No other patients were diagnosed with lung cancer within one year. 1 patient was diagnosed with cancer at a later date (interval 774 days). Nodule surveillance led to a cancer diagnosis in a further 7 patients, including one initially in the probable cancer group. 44 patients were discharged following a normal chest X-ray, with no cancers detected during follow-up. Conclusions: Intrathoracic malignancy was adequately excluded following a normal CT thorax or a CT showing benign changes. Clinicians should enquire about upper airways symptoms and have a low threshold for bronchoscopy in the context of endobronchial abnormalities in patients presenting with haemoptysis. Rates of cancer in the follow-up period are consistent with new cancer rates in high risk patients. References: DOI:10.1183/1393003.congress-2017.PA4274 DOI:10.1016/S0169–5002(15)50044–5